Estrategia didáctica de comprensión de textos y el aprendizaje de equilibrio ecológico en estudiantes de tercer grado de secundaria - Contreras Garcia, Pedro Javier (2019)
The purpose of the present study was to develop and apply a strategy of text comprehension in the achievement of ecological balance learning in third grade students at the secondary level, curricular area of science and technology. For the application of the strategy a learning session was elaborated in which the empirical modeling and systemic methods were applied. In the foundation we worked with the analytical - synthetic, inductive - deductive and comparative theoretical methods. The execution took into account the techniques of the exhibition, the team work, the collaborative work. In the evaluation, the techniques of hetero-evaluation, co-evaluation and self-evaluation were applied. After the conclusion of the session, it was evidenced that the students achieved the ecological balance learning.